FEASIBILITY STUDY OF BUSINESS IN AGARWOOD INOCULATION AT DIFFERENT STEM DIAMETERS AND INOCULATION PERIODS - Sri Suharti; Pratiwi Pratiwi; Erdy Santosa; Maman Turjaman (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2011)
Indonesia signifies as the biggest agarwood producer country in the world. Its demand and price tend to increase and have brought about over exploitation of agarwood. Consequently, its population in nature has decreased significantly. To overcome the situation, since 1995, agarwood has been included in the CITES Appendix II. However, illegal exploitation remains persistent and reaches an excessive level. In order to deal with it, agarwood cultivation and its artificial production have been undertaken at several provinces in Indonesia. Some supporting factors for agarwood cultivation and artificial production are the availability of potential land for extensive cultivation, appropriate agro climate condition, simple cultivation technique and already being well adopted by farmers, the availability of necessary pathogen for agarwood inoculation, and the increasing demand with relatively high price. The research aims to analyze the feasibility study of agarwood inoculation business at several stem diameters (15 - 25 cm; 26 -35 cm and 36 - 40 cm) and periods of inoculation (1 - 5 years). Data were collected through field observation and literature study. The results showed that inoculation on agarwood producer tree stands at 12.5% interest rate afforded positive net present value (NPV), internal rate of return (IRR) is much higher than market interest and benefit cost (B/C) ratio >2 for those three diameter classes. Furthermore, if agarwood harvesting is delayed until five years after inoculation, NPV, IRR and B/C ratio would be much higher. It can be concluded that inoculation on agarwood producer tree stands (at appropriate age for inoculation) is feasible to be developed.